English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Multiply: -5 (x+3)=?. -4 (x - 6) = ?...Explain how you solve....Simplify: -4 (-2 - 4) - (-3)( -3 - (-9)). Simplify: -(-3) - 6 (5 - 2)

2007-01-28 10:59:59 · 4 answers · asked by ilovebasketball 2 in Science & Mathematics Mathematics

Try these too: 6 (9x - 3).. 9 (4x + 3)

2007-01-28 11:45:35 · update #1

4 answers

1. Solve > -5(x + 3)
First: use distribution > multiply the outer term with the terms in parenthesis...

(-5)(x) - (5)(3)
- 5x - 15

2. - 4(x - 6)
First: use distribution - multiply the outer terms with the terms in parenthesis...

(-4)(x) - (4)(-6)
- 4x - (-24)
- 4x + 24

3. Simplify > - 4(-2 - 4) - (-3)( -3 - (-9))

First: use PEMDAS > (), exponents, multiplication, division, addition & subtraction...

- 4(-6) - (-3)(-3 + 9)

24 - (-3)(6)

24 - (-18)

24 + 18
= 42

4. Simplify > -(-3) - 6(5 - 2)

*Use PEMDAS...

-(-3) - 6(3)

-(-3) - 18

3 - 18

= - 15

2007-01-28 11:31:06 · answer #1 · answered by ♪♥Annie♥♪ 6 · 0 0

-5(x+3) = -5x -3 (distributive property, just multiply the number outside the parentheses by each of the numbers inside)

-4(x-6) = -4x -(-24) = -4x+24 (distributive, and minus a negative is a positive)

-4(-2-4) -(-3)(-3-(-9)) = -4(-6) -(-3)(-3+9) = 4(6) + 3(6) = 24 + 18 = 42

-(-3) - 6(5-2) =
--3 - 6(3) =
3 - 18 =
-15

2007-01-28 19:07:21 · answer #2 · answered by Steve A 7 · 0 0

Well you have to follow the rules of PEMDAS (parentheses, exponents, multiplication, division, addition, subtraction) so for the first one -5 (x+3)=?, you would have to multiplay -5 to all the things inside the parentheses, therefore it would be, -5x-15. For the second one, -4 (-2 - 4) - (-3)( -3 - (-9)), okay you start off with the parentheses, so it would be
-4(-6) -(-3)(-3+9)
24+3(6)
24+18
= 42

for the last one, -(-3) - 6 (5 - 2), again parentheses first.
+3-6(3)
+3-18
= -15

hope that helps

2007-01-28 19:07:15 · answer #3 · answered by KaitouKID 2 · 0 0

-5(x+3) = -5X-15 - multiply -5 by x and -5 by 3

-4(x-6) = -4X+24 - multiply -4 by x and -4 by -6 : two negatives multiplied always gives a positive

I'm bored now

2007-01-28 19:08:24 · answer #4 · answered by Bob Danvers-Walker 4 · 0 0

fedest.com, questions and answers